Implementation strategies in suicide prevention: a scoping review - Jason I. Chen; Brandon Roth; Steven K. Dobscha; Julie C. Lowery (2024)
Implementation strategies can be a vital leveraging point for enhancing the implementation and dissemination of evidence-based suicide prevention interventions and programming. However, much remains unknown about which implementation strategies are commonly used and effective for supporting suicide prevention efforts.